Extension on Making Lime Dishwashing Soap With The Addition of Pandan Leaf Extract in Lhoknga Village, Aceh Besar District: Penyuluhan Pembuatan Sabun Cuci Piring Jeruk Nipis dengan Penambahan Ekstrak Daun Pandan di Desa Lhoknga Kabupaten Aceh Besar - Mahmudi, Mahmudi; Farida, Mutia; Azhari, Saiful (Jukeshum: Jurnal Pengabdian Masyarakat, 2025)
This community service activity aims to provide education and training to the people of Lhoknga Village, Aceh Besar Regency, on how to make dishwashing soap from natural ingredients. In this training, lime is used for its effective ability to remove grease and dirt, while pandan leaf extract is added as a refreshing natural fragrance. The training is conducted practically through soap-making sessions, enabling participants to gain not only theoretical knowledge but also hands-on skills in producing soap independently using readily available local materials. Through this initiative, it is hoped that positive impacts will be created for the environment and the local economy, while also fostering awareness of the importance of using environmentally friendly products. Additionally, this training opens opportunities for the development of small-scale businesses based on household products with market value